Functions and Artistic Specificity of Folk Earthenware in Customs and Rituals of the Calendar Cycle of the Ukrainians - Halyna Ivashkiv (EtnoAntropologia, 2020)
The given paper analyzes functions and artistic features of Ukrainian folk earthenware which was used in customs and rituals of the calendar year, predominantly while celebrating the biggest religious holidays, namely Christmas and Easter. In particular, the author explores such items as triple candlesticks, various earthenware meant for blessing holy water, other types of crockery, particularly pots, round pots, jugs, O-shaped flat jars, flat jars, bowls, makitras, doughnut bowls, goose, piglet and fish roasters, Easter bread moulds, baskets, Easter eggs etc. Folk earthenware has been examined through the context of preparations to and celebration of calendar holidays, which were associated with the beliefs the Ukrainian people had, as well as their analogues in other European people’s traditions.